Gratitude intersects with affect as a boundary condition for daily satisfaction: An affective dynamics perspective - Mosteo, L.; Junça Silva, A.; Lopes, M. (Applied Psychology - Health and Well-Being, 2023)
This study is based on the affective events theory to investigate the situational predictors for gratitude-related differences in daily affect and satisfaction. We tested a moderated mediation model in which daily microevents (daily hassles and uplifts) were related to satisfaction through affect, at the within-person level. We also tested the cross-level interaction of gratitude on this indirect relationship. A total of 195 participants participated in a 5-day diary study (195 * 5 = 975 measurement occasions). Multilevel modeling showed that, at the person-level of analysis, daily microevents were significantly related to daily affect and, in turn, to daily satisfaction. At the daily level of analysis, trait-based gratitude moderated the mediation of daily positive affect on the relationship between daily uplifts and daily satisfaction, such that it become stronger for individuals who scored lower on gratitude, but gratitude did not moderate the relationship between daily hassles, negative affect, and satisfaction. These findings make relevant theoretical contributions to understanding the power of gratitude for daily affective dynamics. These results also expand knowledge on within-person processes that explain daily affect and satisfaction, in addition to more traditional between-person factors. In sum, the present research demonstrates that “being grateful” may be associated with being happy and that individuals who are less grateful need to experience more daily uplifts and positive affect to feel satisfied.